Risk factors for delayed-onset dementia after stroke or transient ischemic attack—A five-year longitudinal cohort study. Issue 5 (June 2022) - Ismail, Moamina; Mok, Vincent CT; Wong, Adrian; Au, Lisa; Yiu, Brian; Wang, Zhaolu; Chu, Winnie CW; Chan, Anne YY; Fan, Florence SY; Ma, Sze H; Ip, Vincent; Ip, Bonaventure; et al.
Background: Stroke not only substantially increases the risk of incident dementia early after stroke but also the risk remains elevated years after. Aim: We aimed to determine the risk factors of dementia onset more than three to six months after stroke or transient ischemic attack. Methods: This is a single-center prospective cohort study. We recruited consecutive subjects with stroke/transient ischemic attack without early-onset dementia. We conducted an annual neuropsychological assessment for five years. We investigated the association between baseline demographic, clinical, genetic (APOEɛ4 allele), and radiological factors as well as incident recurrent stroke with delayed-onset dementia using Cox proportional hazards models. Results: In total, 1007 patients were recruited, of which 88 with early-onset dementia and 162 who lost to follow-ups were excluded. Forty-nine (6.5%) out of 757 patients have incident delayed-onset dementia. The presence of ≥3 lacunes, history of ischemic heart disease, history of ischemic stroke, and a lower baseline Hong Kong version of the Montreal Cognitive Assessment (MoCA) score were significantly associated with delayed-onset dementia. APOEɛ4 allele, medial temporal lobe atrophy, and recurrent stroke were not predictive. Conclusion: The presence of ≥3 lacunes, history of ischemic heart disease, history of ischemic stroke, and a lower baseline MoCA score are associated with delayed-onset dementia after stroke/transient ischemic attack.